Morpho-anatomical investigations of three critically endangered endemic species - Küçük, Sevim; Sayarer, Melike (Bangladesh Journal of Botany, 2020)
Morphological and anatomical characteristics of Crocus ancyrensis Herb. (Maw) (endemic), C. antalyensis Mathew (endemic), C. chyrsanthus (Herb.) Herb. and C. sativus L. which are distributed in Central Anatolia, Turkey have been studied. The morphological characteristics of species have been compared with the Flora of Turkey. In anatomical studies, transverse sections of root, stem and leaf have been examined and supported by illustration. In addition, the determination of the anatomical characteristics of the species are given in this study for the first time. The leaf anatomy of Crocus ancyrensis has been illustrated elsewhere.